Carrier preference after graduation among AIIMS nursing students: higher education or government job as nursing officer - Phalswal, Uma; Dixit, Priyanshi; Verma, Ranjana; Rathee, Anjali (International Journal of Research in Medical Sciences, 2023)
Background: Career by choice means that a student chooses a career of their own choice according to their interests and the demands of time. The present study aimed to investigate the preferences of pursuing government jobs or higher education among final-year nursing undergraduates and perceived barriers to pursuing higher education in nursing. Methods: A descriptive cross-sectional web-based study was conducted among 207 final-year B.Sc. nursing students from May 2021 to June 2021 at the various All India Institutes of Medical Sciences of India. Data collection was done using total enumerative sampling techniques by self-structured questionnaire. A descriptive statistic was applied to prepare the results. Results: Findings suggested that the government job after graduation was the priority among students (63.3%), and only (30.4%) of students were highly motivated to pursue higher education in nursing. The majority (42.9%) of respondents given a reason to choose a nursing course were not selected in NEET-UG. Further data revealed that the reason for choosing the job over higher education was financial independence. Findings also reported that the student's perspectives towards the nursing profession were a lack of respect as compared to other medical professions, stigma in society, socially less accepted professions, fewer opportunities in research and education, and gender discrimination in the profession. Conclusions: The findings necessitate the need for a sensitization program to develop awareness of the benefits of pursuing higher education. This may change the stigma and improve the social image of the profession.